Identifying some regularities of the fatigue behavior of the reinforced carbon-fiber with Al2O3 nanoparticles composite structure of the prosthesis foot - Shomran, Ali Talib; Faisal, Batool Mardan; Hussein, Emad Kamil; Santos, Thiago; Fatima, Kies (Eastern-European Journal of Enterprise Technologies, 2023)
In this research Carbon-Fiber with AL2O3 Nanoparticles Composite Structure of the Prosthesis foot has been examined and analysed numerically explain the fatigue behaviour of the prosthesis. Nanoparticles made of AL2O3 were incorporated into the production process of the composite structure of the prosthesis foot in the appropriate manner. The life forecast, the damage indicator, and the Biaxiliray indexation were the three primary considerations that went into the process of studying the composite construction of the prosthesis foot. The life prediction was the most important factor. Experiments on the phenomena of fatigue have been carried out with the stress being entirely reversed as the variable in order to ensure that the findings are in keeping with the theory that was proposed by GoodMan. In order to develop an estimate for these characteristics, the dynamic load that was applied, which was 1000 N, was utilised. It used the dynamic load that was applied in order to produce an estimate for these characteristics so that we could better understand them. The results of the computational research showed that the life prediction could be increased to 106 cycles by applying a primary force of 1000 N. This was shown by the findings of the studyThis was demonstrated by the findings. While the same load application was being carried out, the Biaxiliray indexation attained a value of 0.99. In addition to the research that was done on the damage indicator, the numerical findings demonstrated that the damage can be seen after the initial 1000 cycles of stress have been applied. This was demonstrated both by the research that was done on the damage indicator as well as by the numerical findings